THE LEGIONARY COINS OF SEPTIMIUS SEVERUS - Nathaniel S. KATZ (Journal of Ancient History and Archaeology)
As Severus faced his opponents in the Year of the Five Emperors, his mint produced a series of legionary coins that named each of the legions fighting for him. This article shows how those coins not only celebrated Severus’ soldiers but framed Severus in relation to previous leaders. Previous scholarship has focused on how the coins allude to the most famous series of legionary coins, that of Mark Antony before Actium, but that was not the only connection the coins made. Though not included in the Roman Imperial Coinage descriptions, coins for several of Severus’ legions also include Capricorns, which this article shows were the first of the many ways that Severus connected himself to Augustus. Similarly, Severus’ coins also linked him to Marcus Aurelius, the last emperor to use the iconography of a legionary eagle between standards before Severus himself.